PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATA PELAJARAN IPA DI KELAS III SD N 067240 MEDAN T.P 2024/2025 - Elim Lea Br Ginting; Sri Wahyuni; HJ Khoiriah (STKIP Subang, 2024)
This research aims to improve the science learning outcomes of class III students at SD Negeri 067240 Medan T.P 2024/2025 by using the Make A Match learning model. The form of this research is classroom action research (PTK) using quantitative research using experimental methods. The research results found that student learning outcomes showed only 44% completion and these results were not satisfactory. Student learning outcomes in cycle I with an average score obtained was 70 with a student completion level of 55% and this was said to be quite good. Student learning outcomes in cycle II obtained an average score of 80 with a completion percentage level of 83% which can be said to be very good. The results of the research conducted show that students' science learning outcomes have improved significantly by using the Make A Match learning model.